Application of the Leslie Matrix Model in Predicting Population Growth Rates and Livestock Harvesting - Muntafi’ah, Naailah; Prabowo, Agung; Suroto (International Journal of Mathematics, Statistics, and Computing, 2025)
Leslie matrix model is a population growth model that can be used to predict the number and growth rate of populations that are female in population and female in animals. In animal populations, the Leslie matrix can be used in harvesting. This study aims to apply the Leslie matrix model to predict the number and growth rate of female cattle and determine the proportion of female cattle population harvesting. The female cattle populations used were female dairy cattle and female beef cattle. The results showed that the prediction of female dairy cattle population in 2022 - 2025 decreased every year. As for the female beef cattle population, the prediction results show that the number populaton always increase every year. Furthermore, to determine harvesting is only applied to the female beef cattle population. For uniform harvesting, the result is 11.4% of the population of each class and for the youngest class, the result is 50.5% of the population of the first age class.